Total Phenol and Total Flavonoid of Graded Fractination Fresh and Dried Muntingia calabura Extract: A Sustainable Immunomodulator Bioagent for Functional Health Drink - Mufti Hatur Rahmah; Nurfila Nurfila; Arlinda Puspita Sari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This study aims to determine the total phenol and flavonoid content of fresh cherry leaf extract and dried cherry leaf extract using the stratified maceration extraction method. The approach used in this research is quantitative. The samples in this study were fresh cherry leaves and dried cherry leaves obtained from Somba, Sendana District, Majene Regency, West Sulawesi. The research data were analyzed using the formula for calculating the total compound content. The results of determining the total phenol content of fresh cherry leaf extract and dried cherry leaf extract obtained a wavelength of 600 nm with levels for fresh cherry leaf extract of 303.2 mg GAE/g sample and for dry cherry leaf extract of 320.5 mg GAE/g sample while the content of The total flavonoids of fresh cherry leaf extract and dried cherry leaf extract obtained a wavelength of 415 with levels for fresh cherry leaf extract of 940.6 mg QE/g sample and for dry cherry leaf extract of 987.7 mg QE/g sample. The total content of phenol and flavonoid using the multilevel maceration method in dried cherry leaves was greater than that of fresh cherry leaves (Muntingia calabura)